(untitled) (International Journal of Nursing Education, 2020)
Introduction: Internally displaced people are those who are compelled to escape but they either cannotor do not desire to cross an international border. In addition, internal displacement can affect persons inparticular or an entire groups(1). The most common psychological reactions found in internally displacedpeople in addition to PTSD are depression, somatization, and existential problems(2). It was found that theprevalence of depression symptoms range among displaced individuals was 38%-41%(3).Objective: The study aims to find out levels of depressive symptoms among displaced citizen in Baghdadcity and to find out whether there is any relationship between those levels and some socio-demographiccharacteristics of displaced citizens.Methodology: A descriptive analytic design study was conducted from November 10th, 2017 to the April10th, 2018 with the purpose of assessing the levels of depressive disorder among displaced citizens whotemporarily live in displaced camps in Baghdad city. A non-probability (purposive) sample of 110 of thosedisplaced citizens was recruited to join in present study. To meet the goals of the study a questionnaire wasmade. The questionnaire has two functions: primarily, four socio-demographic characteristics of displacedpeople: gender, age, level of education, and marital status; and furthermore, fifteen items represent GeriatricDepression Scale (GDS-15) for Almeida (1999)(4) which expected to determine the levels of depressivedisorder among the displaced people. Collected data were examined by means of: a descriptive statisticalanalysis: frequencies and percentages and tables of distribution; and inferential analysis which was Chi2.Results: The results indicate that about three quarters of the participants are male; half of them are oftwenties decade of age; about half of those displaced are unmarried; and three quarters of them have primaryand secondary levels of education. And the results reveals too that more than half of displaced citizens havemoderate level (64.5%); and only 11.8% are within normal level of depressive disorder; and nearly quarterof them have severe level (23.6%).Recommendations: The study recommends for the necessity to provide mental health services for displacedcitizens in displacement camps. And an escalation in the extent of mental health and psychosocial supportservices for those displaced citizens. The necessity is needed to sufficiently support and offer broad healthcarefor them.